2017
DOI: 10.1159/000484250
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anti-TNF Therapy on CD4+ and CD8+ Cell Subsets in Ankylosing Spondylitis

Abstract: Objectives: Ankylosing spondylitis (AS) is a chronic, progressive immune-mediated inflammatory disease, driven primarily by Th1 and Th17 cells. Anti-TNF therapies are successfully used in AS to achieve and maintain remission. However, their influence on the composition of T-cell subsets is not clear. We aimed to characterize the changes in the T-cell repertoire after a long-term anti-TNF treatment in AS patients. Methods: Twenty-two AS patients under long-term anti-TNF therapy were evaluated (15 anti-TNF respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
7
17
0
Order By: Relevance
“…Our results showed that Anbainuo injections could address partial immune function imbalance in AS patients by affecting differentiation and activation of immune cell subtypes, including naïve CD4+ T cells, Tregs, and B10 cells. Among these, the decreased proportion of naïve CD4+ T cells after Anbainuo treatment was consistent with the findings of past research [20]. Our observation that naïve We also find that Anbainuo treatment for AS can increase the proportion of negative regulatory cells such as Tregs and Bregs in inflammation that are significantly lower than normal before treatment.…”
Section: Correlation Between Immune Cells and Clinical Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that Anbainuo injections could address partial immune function imbalance in AS patients by affecting differentiation and activation of immune cell subtypes, including naïve CD4+ T cells, Tregs, and B10 cells. Among these, the decreased proportion of naïve CD4+ T cells after Anbainuo treatment was consistent with the findings of past research [20]. Our observation that naïve We also find that Anbainuo treatment for AS can increase the proportion of negative regulatory cells such as Tregs and Bregs in inflammation that are significantly lower than normal before treatment.…”
Section: Correlation Between Immune Cells and Clinical Parameterssupporting
confidence: 92%
“…An increase in Tregs during long-term anti-TNF therapy for AS has also been noted [20]. Our research further reveals a positive correlation between the reduction in CRP value and a higher frequency of Tregs.…”
Section: Correlation Between Immune Cells and Clinical Parameterssupporting
confidence: 81%
“…Despite their widespread use, the impact of TNF-blocking agents on the composition of the adaptive immune system is largely unexplored. In our two previous studies in rheumatoid arthritis (RA) and ankylosing spondylitis (AS), in which anti-TNF therapies are also highly beneficial, we found significant differences in the T-cell subset composition among responder and non-responder patients (Dulic et al 2017(Dulic et al , 2018. Key findings were the normalization of Treg frequencies and the phenotypic pattern of a continuing T-cell activation, as reflected by several activation markers.…”
Section: Introductionmentioning
confidence: 67%
“…Disease-related factors and the effect of biologic drugs must be considered in the assessment of the results. The impact of biologic drugs on T cell repertoire has been reported by Dulic et al [27] . Anti-TNF drugs increases cytokines of Th2 pathways by blocking Th1 pathway [28] .…”
Section: Discussionmentioning
confidence: 85%